Supporting doctors as healthcare quality and safety advocates: Recommendations from the Association of Surgeons in Training (ASiT). (April 2018) - Fleming, C.A.; Humm, G.; Wild, J.R.; Mohan, H.M.; Hornby, S.T.; Harries, R.L.; Fitzgerald, J.E.F.; Beamish, A.J.
Abstract: Background: As front-line healthcare staff, doctors in surgical training occupy a unique organisational space rotating through hospitals and services in which they witness first hand both good and bad practice. This puts trainees in a clear position to identify and raise patient safety issues, and to contribute to discussions regarding quality and safety improvement. However, there are a number of real and perceived barriers to trainees doing so. These include concerns about the impact on training assessments and career progression, and uncertainty about the appropriate route. Methods: Paper-based survey of delegates attending the Association of Surgeons in Training (ASiT) conference (response rate 73%; 479/652). Results: 288 (60%) of trainees reported previous concerns over practices and behaviour of colleagues that might pose risks to patient care including concerns over poor performance (n = 243; 84%), bullying (n = 45; 16%), alcohol and drug abuse (n = 15; 5%) and mental health problems (n = 8; 3%). However, 53% (n = 153) did not escalate these concerns. 178 (37%) of trainees also reported concerns over hospital policies, protocols or systems that might pose a risk to patient care, with 46% (n = 82) not escalating such concerns. Respondents highlighted fear of personal vilification or reprisal (n = 224; 47%), fear of impact on career (n = 206; 43%) and a lack of confidence in the process (n = 170; 36%) as barriers to whistleblowing. More senior trainees were significantly more likely to raise concerns than more junior grades (p < 0.0001). Conclusion: These results highlight worrying issues around reporting concerns, with trainees often "silent witnesses" to poor performance in healthcare. Adverse events must provide opportunities for learning to improve future outcomes. Herein, ASiT proposes 14 recommendations to improve protection for trainees in raising patient safety concerns. These include the creation of a positive workplace culture, promoting the active involvement of trainees in quality improvement discussions, with clear mechanisms for trainees to raise concerns. Highlights: A safety culture is increasingly recognised as an important component to improving healthca re outcomes. Barriers to raising patient safety concerns exist in healthcare, particularly for trainees. Only 16% of the trainees surveyed agreed that the current process of whistleblowing in the NHS is effective at protecting patient safety, or that the current protection for whistleblowers is adequate. Of those trainees that raised concerns only 41% stated that they were satisfied with the response. More robust and safe mechanisms for trainees to feedback on concerns is essential in order to improve patient safety and protect trainees.